Analisis Asosiasi Merek, Nilai Produk, dan Kualitas Pelayanan, Serta Pengaruhnya terhadap Kepuasan dan Loyalitas Konsumen Sepeda Motor di Bekasi - Mohammad Rizan; Harun Arrasyid (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
The objectives of the research are: 1) to describe brand association, product value, service quality, consumer satisfaction and loyalty of motorcycle in Bekasi; 2) to test the influence of brand association, product value and service quality on consumer satisfaction; 3) to test the influence of brand association, product value, and service quality on consumer loyalty; 4) to test the influence of consumer satisfaction on consumer loyalty; 5) to test the simultaneous influence of brand association, product value, service quality on consumer satisfaction and loyalty. The research methods are descriptive and explanatory survey. Population are motorcycle consumer of Honda, Yamaha, and Suzuki in Bekasi. Observation unit are 200 consumer. Sampling technique is proportional stratified random sampling, research instrument is Likert’s questionnaire, and analysis method is Structural Equation Modelling (SEM)/Lisrel 8.7 series. The descriptive research results indicate that dimension which strongly effect on brand association are behavior and benefit. Dimension which strongly effect on product value are cost, exchange value, esthetics and relative function. Dimension which strongly effect on consumer satisfaction are quality and total cost which must be paid. Dimension which strongly effect on consumer loyalty are repurchase, impenetrable to competitor, expand purchase, and recommend. The expalanatory/causal research results indicate that; 1) Brand association, product value, and service quality are significantly influenced on consumer satisfaction (R2=0.86); 2) Brand association, product value, and service quality are significantly influenced on consumer loyalty (R2=0.51); 3) Consumer satisfaction is significantly influenced on consumer loyalty (R2=0.62); 4) Brand association, product value and service quality are direct significantly influenced on consumer loyalty as well as indirectly through consumer satisfaction. Keywords: brand association, product value, service quality, consumer satisfaction, and consumer loyalty.